Effect of prior laser microstructural refinement on the formation of amorphous layer in an Al86Co7.6Ce6.4 alloy - Li, C.L.; Murray, J.W.; Voisey, K.T.; Clare, A.T.; McCartney, D.G. (Elsevier, 2014)
Laser surface melting (LSM) pre-treatment was conducted before large area electron beam (LAEB) treatment in an attempt to eliminate the cracking of the amorphous layer. In our previous work, LAEB treatment successfully generated an amorphous layer on a cast polycrystalline Al-Co-Ce glass forming alloy. However, cracking was found and was associated with large and brittle Al8Co2Ce phase in the bulk material. Results show that prior LSM treatment in this present work can effectively refine the microstructure of as-cast material, decreasing the particle size and particle spacing of Al8Co2Ce phase. This decrease in the microstructural length scale greatly reduced the results of cracking of the amorphous layer. The LAEB pulse number required for the homogenisation and amorphisation of treated layer was also decreased for the laser pre-treated sample compared to as-cast material.